Pengembangan Flashcard SISEMO dalam Memperkaya Kegiatan Bermain Anak dan Orang Tua di Rumah: Development of SISEMO Flashcards to Enrich Play Activities Between Children and Parents at Home - Rani Dwi Kurniawati; Lilis Suryani (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2026)
This study aims to develop "SISEMO" flashcards designed to stimulate the sensorimotor skills of children through parental guidance at home; these flashcards contain ideas for sensorimotor stimulation activities that can be implemented with children in a home setting. The study employs the Research and Development (R&D) method using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, proceeding up to the limited implementation stage for the final product. The analysis phase involved identifying parents' needs regarding play activities with children aged 4–5 years at home through interviews and observations, followed by the design phase, which involved conceptualizing the flashcards. During the development phase, the flashcards were created and validated by subject matter experts, media experts, and practitioners to ensure their suitability. This was followed by three rounds of product testing and revision: individual trials, small-group trials, and large-group trials. Revisions based on feedback resulted in a final model that was implemented on a limited scale at PAUD Al-Hidayah Penjaringan, North Jakarta. The results indicate that the sensorimotor stimulation flashcards are highly suitable for enriching play activities between children and parents at home, achieving validation scores of 95% from subject matter experts, 98% from media experts, and 98% from practitioners. The limited implementation phase, involving children and guardians from Class A at PAUD Al-Hidayah, yielded a questionnaire result of 87.80%. Based on these findings, the sensorimotor flashcards serve as an alternative medium offering sensorimotor stimulation activities that can be carried out with children at home.   ABSTRAK  Penelitian ini bertujuan untuk mengembangkan Pengembangan Flashcard SISEMO untuk Menstimulasi Sensori Motorik Anak dengan Pendampingan Orang Tua di Rumah, Flashcard yang berisi ide-ide kegiatan stimulasi sensori motoric yang dapat di terapkan bersama anak di rumah. Penelitian ini menerapkan metode Research and Development (R&D) dengan model pengembangan (ADDIE) “Analysis, Design, Development, Implementation, Evaluation”. Pada penelitian ini dilakukan hingga tahap Implementasi terbatas untuk penerapan model final produk. Tahap analisis dilakukan dengan mengidentifikasi kebutuhan orangtua dalam penerapan aktivitas bermain bersama anak usia 4-5 tahun di rumah melalui wawancara dan observasi, dilanjutkan tahap desain dengan merancang konsep produk Flashcard. Pada tahap pengembangan, Flashcard di buat dan dilakukan validasi oleh ahli materi, ahli media dan praktisi untuk memastikan kelayakan,  Dilanjutkan dengan 3 uji coba dan revisi produk, yakni uji coba perorangan, kelompok kecil dan uji coba kelompok besar. Lalu merevisi berdasarkan umpan balik sehingga menghasilkan model final untuk di implementasikan secara terbatas di PAUD Al-Hidayah Penjaringan Jakarta Utara. Hasil penelitian menunjukan bahwa Flashcard stimulasi sensori motoric layak di gunakan untuk memperkaya kegiatan bermain anak dan orangtua di rumah dengan kategori sangat layak, skor penilaian ahli materi 95%, ahli media 98% dan ahli praktisi 98%. Tahap implementasi terbatas yang dilakukan oleh anak dan wali murid kelas A paud Al-Hidayah mendapatkan perolehan hasil angket dengan persentase 87,80%. Berdasarkan temuan penelitian ini, Flashcard sensori motorik dapat di jadikan sebagai alternative media yang menyediakan kegiatan-kegiatan stimulasi sensori motoric yang dapat di lakukan bersama anak di rumah.